Premissas normativas para construção da política de catalogação em RDA: estudo de caso no sistema de bibliotecas da UFMG - Cleide Vieira de Faria (2018)
Resource Description and Access (RDA) are standards and guidelines that standardize the description of information resource data in libraries, archives and museum catalogs. The present study addressed the political issue of cataloging in RDA, since the cataloging process in RDA, it is recommended the adoption of this document, which covers technical and institutional decisions, which aim to guide the librarian in the task of describing information resources. As a general objective, the research proposed to establish normative premises, as subsidies for the construction of the cataloging policy in RDA for the Library System of the University Federal of Minas Gerais (SB / UFMG). And, as specific objectives compare the main cataloging rules of AACR2 that had change in the RDA; identify with the cataloging librarians of the institution, which of the main cataloging rules that have been modified and proposed in the RDA should be standardized in the SB / UFMG Cataloging policy and finally, present a proposal of the normative premises to compose the cataloging policy in RDA of SB / UFMG. The research is a case study of exploratory and descriptive nature, with a mixed approach. It was used as an instrument for data collection: bibliographic research, questionnaire and interviews with focus groups. The results identified that, from the RDA rules surveyed, the use of capitals, statement of responsibility and collaborative works and level of detail of the description, were the rules designed to be standardized in the Institution's cataloging policy. The rule edition statement was considered in this study without the need for standardization in the institution's cataloging policy. And, were considered indefinite the rules statement of responsability, extension, and the rules for categorization of resources (RDA 6.9 - content type; 3.2 - media type and e 3.3 – carrier type). The proposal with the normative premises to compose the cataloging policy for SB / UFMG was presented at the end. It is concluded that to elaborate the cataloging policy it is necessary to analyze all the rules of the RDA to apply the local decisions in all the cases that are considered necessary. It is important that the team responsible for the elaboration of the cataloging policy has knowledge about the user and the Institution; experience in the cataloging activity, knowledge of the RDA and AACR2 and the ability to visualize in the catalog the benefits achieved by users with the new standard. It is recommended that the RDA trainings for team that elaborates the cataloging policy.